The Effect of Post-Mastectomy Radiotherapy in Patients With Metaplastic Breast Cancer: A Propensity Score-Matched Analysis of the SEER Database - Hu, Jin; Tan, Jie; Dong, Fang; Zhang, Ximeng; Ming, Jie; Huang, Tao (Frontiers in Oncology, 2022)
Background: Metaplastic breast cancer (MBC) is a rare tumor with aggressive bio-logical behavior. This study aimed to evaluate the efficacy of post-mastectomy radio-therapy (PMRT) on patients with low-risk (T1N0M0), intermediate-risk (T1-2N1M0 and T3N0M0), and high risk (T1-4N2-3M0 and T4N0-1M0) MBC via propensi-ty-score matching (PSM). Methods: We analyzed information from the Surveillance, Epidemiology, and End Results (SEER) public-use database from 1975 to 2016 for MBC incidence trends and compared overall survival (OS) and breast cancer-specific survival (BCSS) between groups of MBC women diagnosed from 2001 to 2016 using Kaplan-Meier analysis and the multivariate Cox proportional model. PSM was used to make 1:1 case-control matching. Results: Joinpoint analyses identified 1984 and 2003 as the inflection points among 4672 patients. 1588 (42.4%) of the 3748 patients diagnosed with MBC between 2001 and 2016 received PMRT. According to multivariate analyses, PMRT provided better OS (p < 0.001) and BCSS (p < 0.001) before PSM, and better prognosis after PSM (n = 2528) for patients receiving PMRT (n = 1264) compared to those without PMRT (OS, p < 0.001 and BCSS, p < 0.001). When stratified the case-control matching pa-tients into low-risk, intermediate-risk, and high-risk groups, PMRT could improve BCSS compared with that in non-PMRT patients in the high-risk groups; it also im-proved OS in both the intermediate- and high-risk groups. Conclusions: Per findings of the PSM analysis, PMRT could provide better BCSS in high-risk groups, and better OS in intermediate- and high-risk groups.